Confessions for Cash: The Consequences of Using Incentivised Witnesses in New Zealand Criminal Cases - McIver, Margaret (Auckland University of Technology, 2023)
Several research studies have examined criminal cases involving incentivised witnesses and the potential for this source of information to contribute to wrongful convictions. These studies focus primarily on witnesses incentivised through a reduction in their criminal charges or prison sentence, such as accomplices and prison informants. However, there is a shortage of literature regarding financially incentivised witnesses and a lack of comparative research on incentivised witnesses overall as well as the legislation governing this type of evidence. This comparative study seeks to analyse all types of incentivised witnesses in the United States of America (US) and Aotearoa New Zealand (NZ) to discuss how the use of incentivised witnesses may contribute to miscarriages of justice in New Zealand, determine whether the use of incentivised witnesses is ethical, and examine whether the current legislation regarding incentivised witnesses is comprehensive enough. The research defines the term incentivised witnesses and discusses how they may contribute to miscarriages of justice. Outlining the history of judicial policy transfer from the US to New Zealand and summarising current legislation in place provides context to the issue. This research analyses secondary sources, including existing academic literature, legislation, court records, and news media, focusing on case studies. The thesis concludes with recommendations of possible changes to legislation in New Zealand regarding the use of incentivised witness evidence, informed by existing research and legislation changes in the US.